Bài Làm:
Lời giải bài 1:
Đề ra :
Cho biểu thức : $T=\frac{3x+\sqrt{16x}-7}{x+2\sqrt{x}-3}-\frac{\sqrt{x}+1}{\sqrt{x}+3}-\frac{\sqrt{x}-3}{\sqrt{x}-1}$ ( Với x > 0)
a. Rút gọn biểu thức T .
b. Tính giá trị của biểu thức T khi $x=2\sqrt{2}+3$ .
Lời giải chi tiết :
a. $T=\frac{3x+\sqrt{16x}-7}{x+2\sqrt{x}-3}-\frac{\sqrt{x}+1}{\sqrt{x}+3}-\frac{\sqrt{x}-3}{\sqrt{x}-1}$
<=> $T=\frac{3x+4\sqrt{x}-7}{(\sqrt{x}+3)(\sqrt{x}-1)}-\frac{\sqrt{x}+1}{\sqrt{x}+3}-\frac{\sqrt{x}-3}{\sqrt{x}-1}$
<=> $T=\frac{3x+4\sqrt{x}-7-(\sqrt{x}+1)(\sqrt{x}-1)-(\sqrt{x}-3)(\sqrt{x}+3)}{(\sqrt{x}+3)(\sqrt{x}-1)}$
<=> $T=\frac{3x+4\sqrt{x}-7-x+1-x+9}{(\sqrt{x}+3)(\sqrt{x}-1)}$
<=> $T=\frac{x+4\sqrt{x}+3}{(\sqrt{x}+3)(\sqrt{x}-1)}$
<=> $T=\frac{(\sqrt{x}+3)(\sqrt{x}+1)}{(\sqrt{x}+3)(\sqrt{x}-1)}$
<=> $T=\frac{\sqrt{x}+1}{\sqrt{x}-1}$
Vậy $T=\frac{\sqrt{x}+1}{\sqrt{x}-1}$ .
b. Ta có : $x=2\sqrt{2}+3=(\sqrt{2}+1)^{2}=> \sqrt{x}=\sqrt{2}+1$
Khi đó thay vào T ta được : $T=\frac{\sqrt{x}+1}{\sqrt{x}-1}=\frac{\sqrt{2}+1+1}{\sqrt{2}-1+1}$
<=> $T=\frac{\sqrt{2}+2}{\sqrt{2}}=1+\sqrt{2}$ .
Vậy khi $x=2\sqrt{2}+3$ => $T=1+\sqrt{2}$ .